Development of facial emotion recognition system using a modified particle swarm optimization technique - Bashir Mohammed Ghandi (School of Mechatronics Engineering, 2012)
The goal of this research is to design an efficient Artificial Intelligence (AI) technique that can be used to implement a software system that can recognize the basic human emotions.